AI Competencies Through the Lens of Systems Thinking Integration in Pre-service Teachers’ Education - Hadjileontiadou, Sofia; Kaspidis, Ioannis; Tsetsiou, Eirini (Συνέδρια της Ελληνικής Επιστημονικής Ένωσης Τεχνολογιών Πληροφορίας & Επικοινωνιών στην Εκπαίδευση, 2026)
This paper presents a flexible, generic conceptual framework, combining the Cynefin model and feedback loops, to develop systems thinking and AI competencies in Gen Z pre-service teachers. Serving as both a learning design space and a foundation for educational materials, it supports preparing future educators to navigate complexity and address sustainability challenges in evolving societal contexts.